Non-classical functions of nuclear pore proteins in ciliopathy - Chen, Yan; Zhang, Yuan; Zhou, Xiangyu (Frontiers in Molecular Biosciences, 2023)
Nucleoporins (NUPs) constitute integral nuclear pore protein (NPC) elements. Although traditional NUP functions have been extensively researched, evidence of additional vital non-NPC roles, referred to herein as non-classical NUP functions, is also emerging. Several NUPs localise at the ciliary base. Indeed, Nup188, Nup93 or Nup205 knockdown results in cilia loss, impacting cardiac left–right patterning in models and cell lines. Genetic variants of Nup205 and Nup188 have been identified in patients with congenital heart disease and situs inversus totalis or heterotaxy, a prevalent human ciliopathy. These findings link non-classical NUP functions to human diseases. This mini-review summarises pivotal NUP interactions with NIMA-related kinases or nephronophthisis proteins that regulate ciliary function and explores other NUPs potentially implicated in cilia-related disorders. Overall, elucidating the non-classical roles of NUPs will enhance comprehension of ciliopathy aetiology.